Simuliidae (Diptera) of the Solomon Islands: new records and species, ecology, and biogeography - Craig, D. A.; Englund, R. A.; Takaoka, H. (Zootaxa, 2006)
Five species of Simuliidae are reported for the first time from the Solomon Islands of Santa Isabel, Malaita, and Makira, and Kolumbangara and Rendova of the New Georgia Island group. One newspecies, Simulium (Gomphostilbia) rhopaloides Craig, Englund & Takaoka, from Guadalcanal is described. The new material consists mainly of immature larvae, which, while allowing assignment to subgenus, do not always allow identification to species. The probability of other new species is suggested. The record for Makira is the most easterly known for the subgenus Morops, as are those for Gomphostilbia from Guadalcanal and Malaita. Larval habitats on the islands are illustrated. A brief synopsis of the paleogeology of the Solomon Islands is given as a basis for preliminary comments on distribution and biogeography of the known species of Simuliidae, now 10, for the Solomon Islands.